Tinjauan Yuridis Terhadap Permohonan Dispensasi Nikah Pasca Berlakunya Undang-Undang Nomor 16 Tahun 2019 Perkawinan - Destriyanti, Shafira Salwa (Proceedings Series on Social Sciences & Humanities, 2024)
Marriage is the right of every person who aims to form a family by a husband and wife as regulated in article 1 of Law Number 1 of 1974 concerning Marriage that Marriage is a physical and spiritual bond between a man (husband) and a woman (isrti) whose aim is to form a happy and eternal family (household) based on belief in Almighty God. However, along with the dynamics that are developing in society, currently there are many underage marriages or what is often referred to as early age marriages. Early Marriage can be interpreted as a marriage that takes place even though they are still children. The age limit for marriage is regulated in article 7 paragraph (1) of Law Number 16 of 2019 concerning Marriage which states that marriage is only permitted if the man and woman have reached the age of 19 (nineteen) years. This research uses a Normative Juridical method, which means that this research is based on searches with reference to and based on norms, legislation, legal theories and doctrines, court decisions and other library materials that are relevant and in accordance with the topic discussed in this research.